Pnmt-Derived Cardiomyocytes: Anatomical Localization, Function and Future Perspectives - Fan, Xuehui; Sun, Tianyi; Crawford, William; Tan, Xiaoqiu; Ou, Xianhong; Terrar, Derek A.; Ebert, Steven N.; Lei, Ming (Frontiers in Physiology, 2019)
In this mini-review, we provide an overview of phenylethanolamine-N-methyl transferase (Pnmt)-derived cardiomyocytes (PdCMs), a recently discovered cardiomyocyte subpopulation. We discuss their anatomical localization, physiological characteristics, possible function and future perspectives. Their unique distribution in the heart, electrical activity, Ca2+ transient properties and potential role in localized adrenergic signalling are discussed.